2014
DOI: 10.1021/ja5016958
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein-Induced Membrane Remodeling Is Driven by Binding Affinity, Partition Depth, and Interleaflet Order Asymmetry

Abstract: We have investigated the membrane remodeling capacity of the N-terminal membrane-binding domain of α-synuclein (α-Syn100). Using fluorescence correlation spectroscopy and vesicle clearance assays, we show that α-Syn100 fully tubulates POPG vesicles, the first demonstration that the amphipathic helix on its own is capable of this effect. We also show that at equal density of membrane-bound protein, α-Syn has dramatically reduced affinity for, and does not tubulate, vesicles composed of a 1:1 POPG:POPC mixture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
111
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(121 citation statements)
references
References 73 publications
7
111
2
1
Order By: Relevance
“…As expected, the headgroup density is higher in the inner leaflet due to compaction in the convex vesicle. The protein has very little effect on bilayer structure, partitioning to a similar depth as previous studies (6,9,10,17), with no notable change in bilayer thickness (Fig. S1 in the Supporting Material).…”
supporting
confidence: 72%
“…As expected, the headgroup density is higher in the inner leaflet due to compaction in the convex vesicle. The protein has very little effect on bilayer structure, partitioning to a similar depth as previous studies (6,9,10,17), with no notable change in bilayer thickness (Fig. S1 in the Supporting Material).…”
supporting
confidence: 72%
“…When sufficient chemical information is retained, coarse-grained models can discriminate between different lipids and distinguish protein residues, and thus form a useful bridge between atomistic and macroscopic data. For instance, one can now simulate the collective lipid-mediated selfassembly of membrane proteins (Benjamini and Smit, 2013;Hall et al, 2012;Johnston et al, 2012;Periole et al, 2012;van den Bogaart et al, 2011) and their sorting between different membrane domains (de Jong et al, 2013;Janosi et al, 2012;Schäfer et al, 2011), as well as large-scale protein-induced membrane remodelling -including fusion and fission events (Baoukina and Tieleman, 2010;Braun et al, 2014;Davies et al, 2012;Fuhrmans and Müller, 2015;Kawamoto et al, 2015;Pinot et al, 2014;Risselada et al, 2014;Simunovic et al, 2013).…”
Section: Coarse-grain Resolutionmentioning
confidence: 99%
“…Recently, it has been shown that all three human synucleins, α, β and γ 52 , induce the tubulation of vesicles composed of brain polar lipids, at concentrations estimated to be physiologically relevant 31 . In vitro, the remodelling activity is most efficient when pure negatively charged membranes are involved 27,30,32,53 . The fact that α-Syn shares common features with known curvature-inducing protein and with apolipoproteins suggests shared functionalities and a direct involvement of α-Syn in vesicle trafficking and lipid transport/storage.…”
Section: Physiological Relevance Of the Membrane Remodelling Activitymentioning
confidence: 99%